2017
DOI: 10.1016/j.nicl.2016.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Network interactions underlying mirror feedback in stroke: A dynamic causal modeling study

Abstract: Mirror visual feedback (MVF) is potentially a powerful tool to facilitate recovery of disordered movement and stimulate activation of under-active brain areas due to stroke. The neural mechanisms underlying MVF have therefore been a focus of recent inquiry. Although it is known that sensorimotor areas can be activated via mirror feedback, the network interactions driving this effect remain unknown. The aim of the current study was to fill this gap by using dynamic causal modeling to test the interactions betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 86 publications
(113 reference statements)
4
57
0
Order By: Relevance
“…Another study enrolled both patients who have had strokes and brain tumors, and the data of stroke participants could not be separated; these studies were hence excluded [ 16 , 44 ]. Finally, 19 articles satisfied our inclusion criteria and were included in the present review [ 13 , 22 , 28 , 34 , 45 – 59 ]. Figure 1 shows the identification process for the selection of studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study enrolled both patients who have had strokes and brain tumors, and the data of stroke participants could not be separated; these studies were hence excluded [ 16 , 44 ]. Finally, 19 articles satisfied our inclusion criteria and were included in the present review [ 13 , 22 , 28 , 34 , 45 – 59 ]. Figure 1 shows the identification process for the selection of studies.…”
Section: Resultsmentioning
confidence: 99%
“…Eight articles explored the concurrent effects of AO or action execution with MVF on brain activation, evidenced by fMRI [ 34 , 47 , 48 , 50 , 53 , 55 – 57 ]. In studies regarding MVF, Michielsen et al found that bimanual movement with MVF led to significant activation of the precuneus and the posterior cingulate cortex (PCC), rather than the MNS [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Saleh et al, 2017 Single Intervention: A VR goal-directed finger flexion movement with their unaffected hand while observing real-time visual feedback of the corresponding (veridical) or opposite (mirror) hand.fMRIStanden et al, 2017 Eight Weeks Training: Randomly divided into 2 conditions: (1) VR employing infrared capture to translate the position of the hand into gameplay or usual care;(2) Control -usual care. (1) Wolf Motor Function Test;(2) Nine-Hole Peg Test;(3) Motor Activity Log; (4) Nottingham Extended Activities of Daily Living.…”
mentioning
confidence: 99%
“…VMF is a commonly employed regimen in rehabilitation wherein patients receive visual input of the movement while the movement is being executed . It has been proposed that the training‐inducing effects of VMF arise from enriching the visual and proprioceptive inputs to the MNS . MI is defined as the dynamic mental execution of an action, without its actual motor execution …”
Section: Introductionmentioning
confidence: 99%